Aesthetic politics and community gardens in Singapore. Issue 10 (26th November 2021) - Montefrio, Marvin Joseph F.; Lee, Xin Run; Lim, Elwin
ABSTRACT: This paper explores the complexities of aesthetic politics in urban geographies using the case of community gardens in Singapore. Drawing from qualitative research, our findings suggest that community gardeners in Singapore attend to aesthetics – in particular the order and beauty of production spaces – in response to expectations and pressures anchored to the realities of a manicured "green" cityscape. These pressures are enforced not only by the juridical and executive powers of governmental and institutional authorities, but also through the diffused power of the "aesthetic gaze" – a set of aesthetic expectations that emanate from multiple actors across hierarchies to discipline community gardeners. However, rather than merely comply, community gardeners are aware of the impacts of aesthetic expectations on their everyday gardening and therefore are able to negotiate, and at times resist, these powers with varying degrees of agency and strategy.